A simplified method for determination of the soil–water characteristic curve variables. Issue 4 (4th July 2019) - Soltani, Amin; Azimi, Mahdieh; Deng, An; Taheri, Abbas
Abstract: The air-entry value and residual state suction are two critical variables obtained from the soil–water characteristic curve (SWCC). An accurate determination of these variables is essential for the prediction of unsaturated soil properties. Currently, these variables are obtained by a conventional graphical method, which is implemented to the fitted SWCC. The graphical method is associated with subjective uncertainty, leading to inconsistent results. This study presents a new method to determine the air-entry value and residual state suction. Explicit equations are established with respect to four common van Genuchten (vG) SWCC model classes. The relationships between the air-entry value and fitting parameters are analysed using a compiled database of varying soil textural classes. The proposed equations outperform the graphical method by avoiding subjective judgements. Finally, ANOVA and sensitivity analyses are conducted to compare the advantages of the existing model classes in determination of the air-entry value.